Zirconia frame reinforced polytetrafluoroethylene bionic composite material and preparation method thereof

By introducing an ordered porous zirconia ceramic frame into the polytetrafluoroethylene material and preparing bionic composite materials using directional refrigeration technology, the problems of low load-bearing capacity and poor wear resistance of polytetrafluoroethylene self-lubricating composite materials are solved, and high load-bearing is achieved Significant improvement in capability and wear resistance.

CN116874957BActive Publication Date: 2025-02-14SOUTHWEST JIAOTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310870754.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-17
Publication Date
2025-02-14
Estimated Expiration
2043-07-17

AI Technical Summary

Technical Problem

The existing polytetrafluoroethylene self-lubricating composite materials have low load-bearing capacity and poor wear resistance, making them difficult to effectively use in industrial applications.

Method used

The ordered porous zirconia ceramic frame is combined with the polytetrafluoroethylene filler to prepare a zirconia frame with high load-bearing capacity and wear resistance through directional refrigeration technology.

Benefits of technology

It significantly improves the load-bearing capacity and wear resistance of the material, maintains excellent self-lubricating performance, and is suitable for industrial lubrication.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116874957B_ABST
    Figure CN116874957B_ABST
Patent Text Reader

Abstract

The invention discloses a zirconia frame reinforced polytetrafluoroethylene bionic composite material and a preparation method thereof. The zirconia frame reinforced polytetrafluoroethylene bionic composite material is composed of an ordered porous zirconia ceramic frame and a polytetrafluoroethylene filler, and the preparation steps mainly include preparing the ordered porous zirconia ceramic frame by using an improved directional freezing technology of zirconium acetate and impregnating and sintering the polytetrafluoroethylene. The bionic composite material of the invention utilizes a bionic microstructure composed of an ordered porous zirconia ceramic frame with high load-bearing capacity and a polytetrafluoroethylene filler with a self-lubricating function, and while ensuring the excellent self-lubricating performance of the material, the material load-bearing capacity and wear resistance are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of self-lubricating wear-resistant materials, and in particular relates to a zirconium oxide frame reinforced polytetrafluoroethylene bionic composite material and a preparation method thereof. Background Art

[0002] Lubrication is the main means to reduce friction and wear on the surface of mechanical parts, and is of great significance to ensure the safe operation of equipment, extend the service life of parts, and save materials and energy. Compared with traditional lubrication technology (liquid lubrication and semi-solid lubrication), solid self-lubrication has the advantages of high load-bearing capacity and strong adaptability to working conditions (especially extreme working conditions such as high temperature, high speed, heavy load and vacuum), and it also helps to simplify the equipment structure design and reduce the equipment manufacturing cost. Therefore, it is widely used in high-tech fields such as aerospace, ships and warships, biomedical engineering and precision electronic equipment.

[0003] The core of solid self-lubricating technology lies in the design and preparation of high-performance self-lubricating materials. Polytetrafluoroethylene is one of the solid materials with the lowest friction coefficient at present, and has excellent self-lubricating properties. It can quickly form a self-lubricating transfer film on the contact interface during the friction process, reducing the friction force of the contact interface. However, polytetrafluoroethylene has poor mechanical properties, poor wear resistance, and is prone to mechanical friction damage, so it is difficult to directly apply it to engineering practice.

[0004] At present, the solutions to the poor wear resistance of polytetrafluoroethylene are mainly focused on adding reinforcement particles or continuous fiber fabrics to the polytetrafluoroethylene matrix. In terms of adding reinforcement particles, inorganic rigid fillers such as bronze, graphite, oxide ceramic particles, glass fiber and carbon fiber are mainly added to the polytetrafluoroethylene matrix to improve the overall stiffness and hardness of the material and reduce the surface wear of the material; in terms of adding continuous fiber fabrics, polytetrafluoroethylene is mainly filled into fiber cloths such as aramid or glass cloth, and the material's load-bearing capacity and wear resistance are improved by using the fabric structure with relatively high order and tightness. However, the improvement of the mechanical properties and wear resistance of composite materials by dispersed rigid filler particles and loose fiber fabrics is very limited, and may also lead to a decrease in the self-lubricating properties of the material. Studies have pointed out that due to the insufficient load-bearing capacity of the fiber fabric, the polytetrafluoroethylene matrix is ​​easily removed by excessive wear during the friction process, resulting in the exposure of the fiber fabric, and the rigid fiber is very easy to scratch the surface of the friction pair, destroying the self-lubricating transfer film, resulting in lubrication failure. Summary of the invention

[0005] In order to overcome the problems of low load-bearing capacity and poor wear resistance of existing polytetrafluoroethylene self-lubricating composite materials, the present invention provides a zirconia frame reinforced polytetrafluoroethylene bionic composite material and a preparation method thereof.

[0006] The invention discloses a zirconia framework reinforced polytetrafluoroethylene bionic composite material, which is composed of an ordered porous zirconia ceramic framework and polytetrafluoroethylene filler. The zirconia ceramic framework is 3 mol% yttria-stabilized tetragonal zirconia, and the polytetrafluoroethylene filler content is 70-80 vol%. The surface Vickers hardness of the bionic composite material is ≥40 HV. 1Kgf , elastic modulus ≥8000MPa.

[0007] The method for preparing a zirconium oxide framework reinforced polytetrafluoroethylene bionic composite material of the present invention comprises the following steps:

[0008] Step 1: ceramic slurry preparation: weigh a certain amount of ceramic powder, zirconium acetate, polyvinyl alcohol solution, sodium polyacrylate solution, polyether defoamer and deionized water to prepare a ceramic slurry, wherein the ceramic powder content is 40.0-60.0wt%, the zirconium acetate content is 5.0-7.0wt%, the polyvinyl alcohol solution content is 1.2-1.8wt%, the sodium polyacrylate solution content is 0.2-0.3wt%, and the polyether defoamer content is 0.5-1.0wt%; use a planetary ball mill to mix the ceramic slurry, the ball milling time is 10-18h, and the rotation speed is 280-310r / min; after the ball milling, the ceramic slurry is vacuum degassed for 1-2h, and the vacuum degree is ≤-1.0Mpa.

[0009] Step 2: Preparation of zirconia ceramic frame: Place the mold in a directional freezing device and precool it to -40 to -60°C, then inject the ceramic slurry into the mold, freeze it for 15 to 20 minutes, and finally vacuum freeze-dry it for 24 to 48 hours to obtain a ceramic blank; place the ceramic blank in a silicon-molybdenum rod sintering furnace, heat it to 400 to 600°C, keep it warm for 2 to 3 hours, then continue to heat it to 1500 to 1600°C, keep it warm for 2 to 3 hours, and finally cool it to 300 to 400°C and cool it with the furnace to obtain an ordered porous zirconia ceramic frame.

[0010] Step 3: polytetrafluoroethylene impregnation and sintering: place the ceramic frame in a polytetrafluoroethylene dispersion for vacuum impregnation treatment, the treatment time is 1 to 2 hours, and the vacuum degree is ≤-1.0Mpa; then place the zirconia ceramic frame impregnated with the polytetrafluoroethylene dispersion in an oven, dry for 24 to 48 hours, the drying temperature is 90 to 120°C, and finally place it in a silicon-molybdenum rod sintering furnace, heat it to 300 to 380°C, keep it warm for 0.5 to 1 hour and cool it with the furnace to obtain a zirconium oxide-polytetrafluoroethylene bionic composite material.

[0011] Furthermore, in step 1, the ceramic powder is composed of 85.0-90.0wt% zirconium dioxide, 5.0-10.0wt% aluminum oxide, 1.0-2.0wt% titanium dioxide, 1.0-2.0wt% silicon dioxide and 1.0-2.0wt% cerium dioxide nanoparticles, and the particle size is 30-100nm.

[0012] Furthermore, the zirconium dioxide powder is yttria-stabilized tetragonal zirconium dioxide crystal particles.

[0013] Furthermore, the mass fraction of polyvinyl alcohol in the polyvinyl alcohol solution is 5.0-10.0 wt %.

[0014] Furthermore, the mass fraction of sodium polyacrylate in the sodium polyacrylate solution is 40.0-50.0wt%.

[0015] Furthermore, the heating rate and cooling rate during the sintering process in step 2 are both 5 to 10° C. / min.

[0016] Furthermore, the heating rate during the sintering process in step 3 is 5 to 10° C. / min.

[0017] Furthermore, in step 3, the mass fraction of the polytetrafluoroethylene dispersion is 40.0-60.0 wt %, and the particle size of the polytetrafluoroethylene particles contained therein is 0.2-0.3 μm.

[0018] Beneficial technical effects of the present invention:

[0019] 1) The present invention proposes a novel wear-resistant self-lubricating composite material, which solves the problems of low load-bearing capacity and poor wear resistance of conventional polytetrafluoroethylene self-lubricating composite materials by using an ordered porous zirconia ceramic framework with high load-bearing capacity as the load-bearing phase. At the same time, the ordered porous zirconia ceramic framework has a high porosity (≥70 vol%) and can effectively accommodate polytetrafluoroethylene fillers with self-lubricating function to ensure that a self-lubricating transfer film is formed on the contact interface during the friction process, thereby realizing wear-resistant and self-lubricating materials, and has great application prospects in the field of industrial lubrication.

[0020] 2) Conventional directional freezing technology can only prepare flaky ceramic frames with relatively low load-bearing capacity and strength. The present invention adds zirconium acetate to the ceramic slurry to regulate the growth orientation of ice crystals during directional freezing, prepares an ordered porous zirconia ceramic frame with high load-bearing capacity, and fills polytetrafluoroethylene with self-lubricating function on this basis to prepare a self-lubricating composite material with a bionic microstructure. The material preparation process provided by the present invention is simple and controllable, the required equipment is common equipment in this field, the raw materials used are cheap, non-toxic and pollution-free, and are easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a schematic diagram of the structure of the zirconium oxide frame reinforced polytetrafluoroethylene bionic composite material of the present invention.

[0022] Figure 2 This is an optical photograph of the zirconia frame reinforced polytetrafluoroethylene bionic composite material of the present invention.

[0023] Figure 3 This is a scanning electron microscope photograph of the surface of the zirconium oxide frame reinforced polytetrafluoroethylene bionic composite material of the present invention.

[0024] Figure 4 This is a cloud diagram of element distribution on the surface of the zirconium oxide frame reinforced polytetrafluoroethylene bionic composite material of the present invention.

[0025] Figure 5 The Vickers hardness and elastic modulus of the polytetrafluoroethylene and zirconium oxide frame reinforced polytetrafluoroethylene bionic composite material of the present invention.

[0026] Figure 6 Average friction coefficient and wear volume of the surfaces of polytetrafluoroethylene and zirconia framework reinforced polytetrafluoroethylene biomimetic composites. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0028] A zirconium oxide frame reinforced polytetrafluoroethylene bionic composite material of the present invention is as follows Figure 1 As shown, it is composed of an ordered porous zirconia ceramic frame 1 and a polytetrafluoroethylene filler 2. The zirconia ceramic frame 1 is 3 mol% yttria-stabilized tetragonal zirconia, and the content of the polytetrafluoroethylene filler 2 is 70-80 vol%. The surface Vickers hardness of the bionic composite material is ≥40 HV 1Kgf , elastic modulus ≥ 8000MPa. The optical photos, scanning electron microscope photos and element distribution cloud diagrams of bionic composite materials are shown in Figure 2 , Figure 3 , Figure 4 The bionic composite material of the present invention utilizes a bionic microstructure composed of an ordered porous zirconia ceramic frame with high load-bearing capacity and a polytetrafluoroethylene filler with a self-lubricating function, which greatly improves the material's load-bearing capacity and wear resistance while ensuring the material's excellent self-lubricating performance.

[0029] The preparation method of a zirconium oxide framework reinforced polytetrafluoroethylene bionic composite material of the present embodiment comprises the following steps:

[0030] 1) Weigh 50.0wt%, 6.0wt%, 1.5wt%, 0.3wt%, 0.5wt% and 41.7wt% of ceramic powder, zirconium acetate, polyvinyl alcohol solution, sodium polyacrylate solution, polyether defoamer and deionized water, place them in a planetary ball mill, and mill them at a speed of 300r / min for 12h to obtain a ceramic slurry.

[0031] 2) The ceramic slurry is subjected to vacuum degassing treatment for 1 hour with a vacuum degree of ≤-1.0 MPa.

[0032] 3) The ceramic slurry obtained in step 2) is injected into a mold precooled to -45°C in a directional freezing device, frozen for 15 minutes, and then vacuum freeze-dried for 24 hours to obtain a ceramic blank.

[0033] 4) The ceramic blank is placed in a silicon-molybdenum rod sintering furnace, heated to 400°C, kept warm for 2 hours, then heated to 1500°C, kept warm for 2 hours, and finally cooled to 400°C and cooled with the furnace to obtain an ordered porous zirconia ceramic framework. The heating rate and cooling rate during the sintering process are both 5°C / min.

[0034] 5) The zirconia ceramic frame is placed in a polytetrafluoroethylene dispersion for vacuum impregnation treatment, the treatment time is 0.5 h, and the vacuum degree is ≤-1.0 MPa.

[0035] 6) Place the zirconia ceramic frame impregnated with the polytetrafluoroethylene dispersion in an oven and dry it for 24 hours at a drying temperature of 100°C.

[0036] 7) placing the zirconia ceramic frame impregnated with the polytetrafluoroethylene dispersion obtained in step 6) in a silicon-molybdenum rod sintering furnace, heating it to 380° C., keeping it warm for 0.5 h and cooling it with the furnace to obtain a zirconia frame reinforced polytetrafluoroethylene bionic composite material. The heating rate during the sintering process is 5° C. / min.

[0037] Performance Test:

[0038] 1) Surface hardness test: A KELITI000ZB microhardness tester (Sichuan Kelit Intelligent Technology Co., Ltd.) was used to test the Vickers hardness of the surface of the zirconia frame reinforced polytetrafluoroethylene bionic composite material. The normal load was 1 kgf and the holding time was 15 s.

[0039] The test results are as follows Figure 5 As shown: Compared with polytetrafluoroethylene, the surface Vickers hardness of the zirconia frame reinforced polytetrafluoroethylene bionic composite material is increased by about 7.8 times.

[0040] 2) Elastic modulus test: The elastic modulus of the zirconia frame reinforced polytetrafluoroethylene bionic composite material was tested using a uniaxial compression test using an Instron E1000 electronic universal testing machine (Instron, USA). During the test, the pressure head drop rate was 0.5 mm / min, and the test sample size was 4×4×8 mm. 3 .

[0041] The test results are as follows Figure 5 As shown: Compared with polytetrafluoroethylene, the elastic modulus of the zirconia frame reinforced polytetrafluoroethylene bionic composite material is increased by about 32 times.

[0042] 3) Reciprocating sliding friction and wear test: The tribological properties of the zirconia frame reinforced polytetrafluoroethylene bionic composite material were tested using a UMT-TriboLab multifunctional friction and wear tester (Brook Company, USA). The test used a ball-plane contact mode, a 10mm diameter GCr15 bearing steel ball as the friction pair, a normal load of 7N, a reciprocating displacement of 10mm, a frequency of 2Hz, and a cycle number of 7200 times.

[0043] The test results are as follows Figure 6 As shown: Compared with polytetrafluoroethylene, the average friction coefficient of the surface of the zirconia frame reinforced polytetrafluoroethylene bionic composite material increased by about 11.71%, still showing excellent self-lubricating properties, the wear volume decreased by about 99.95%, and the wear resistance was greatly improved.

[0044] In summary, in the specific implementation of the present invention, a novel zirconium oxide framework reinforced polytetrafluoroethylene composite material with a bionic microstructure is prepared based on a directional freezing technology improved by zirconium acetate. The preparation process is simple and controllable, the required equipment is common equipment in the field, the raw materials used are cheap, non-toxic and pollution-free, and easy to mass produce. At the same time, the zirconium oxide framework reinforced polytetrafluoroethylene bionic composite material of the present invention has both excellent self-lubricating properties and wear resistance, overcomes the bottleneck problems of low load-bearing capacity and poor wear resistance of traditional polytetrafluoroethylene self-lubricating composite materials, realizes wear-resistant and self-lubricating materials, and has great application prospects in the field of industrial lubrication.

Claims

1. A zirconia framework reinforced polytetrafluoroethylene bionic composite material, characterized in that: It is composed of an ordered porous zirconia ceramic frame (1) and a polytetrafluoroethylene filler (2), wherein the zirconia ceramic frame (1) is 3 mol% yttria-stabilized tetragonal zirconia, and the content of the polytetrafluoroethylene filler (2) is 70-80 vol%; The surface Vickers hardness of the bionic composite material is ≥40HV 1Kgf , elastic modulus ≥8000MPa.

2. The method for preparing a zirconia framework reinforced polytetrafluoroethylene bionic composite material according to claim 1, characterized in that: The following steps are involved: Step 1: ceramic slurry preparation: weigh a certain amount of ceramic powder, zirconium acetate, polyvinyl alcohol solution, sodium polyacrylate solution, polyether defoamer and deionized water to prepare a ceramic slurry, wherein the ceramic powder content is 40.0-60.0wt%, the zirconium acetate content is 5.0-7.0wt%, the polyvinyl alcohol solution content is 1.2-1.8wt%, the sodium polyacrylate solution content is 0.2-0.3wt%, and the polyether defoamer content is 0.5-1.0wt%; use a planetary ball mill to mix the ceramic slurry, the ball milling time is 10-18h, and the rotation speed is 280-310r / min; after the ball milling, the ceramic slurry is subjected to vacuum degassing treatment, the treatment time is 1-2h, and the vacuum degree is ≤-1.0Mpa; Step 2: Preparation of zirconia ceramic frame: Place the mold in a directional freezing device and precool it to -40 to -60°C, then inject the ceramic slurry into the mold, freeze it for 15 to 20 minutes, and finally vacuum freeze-dry it for 24 to 48 hours to obtain a ceramic blank; place the ceramic blank in a silicon-molybdenum rod sintering furnace, heat it to 400 to 600°C, keep it warm for 2 to 3 hours, then continue to heat it to 1500 to 1600°C, keep it warm for 2 to 3 hours, and finally cool it to 300 to 400°C and cool it with the furnace to obtain an ordered porous zirconia ceramic frame; Step 3: polytetrafluoroethylene impregnation and sintering: place the ceramic frame in a polytetrafluoroethylene dispersion for vacuum impregnation treatment, the treatment time is 1 to 2 hours, and the vacuum degree is ≤-1.0Mpa; then place the zirconia ceramic frame impregnated with the polytetrafluoroethylene dispersion in an oven, dry for 24 to 48 hours, the drying temperature is 90 to 120°C, and finally place it in a silicon-molybdenum rod sintering furnace, heat it to 300 to 380°C, keep it warm for 0.5 to 1 hour and cool it with the furnace to obtain a zirconium oxide-polytetrafluoroethylene bionic composite material.

3. The method for preparing a zirconium oxide framework reinforced polytetrafluoroethylene bionic composite material according to claim 2, characterized in that: The ceramic powder in step 1 is composed of 85.0-90.0wt% zirconium dioxide, 5.0-10.0wt% aluminum oxide, 1.0-2.0wt% titanium dioxide, 1.0-2.0wt% silicon dioxide and 1.0-2.0wt% cerium dioxide nanoparticles, and the particle size is 30-100nm.

4. The method for preparing a zirconia framework reinforced polytetrafluoroethylene bionic composite material according to claim 3, characterized in that: The zirconium dioxide powder is tetragonal zirconium dioxide crystal particles stabilized by yttria.

5. The method for preparing a zirconia framework reinforced polytetrafluoroethylene bionic composite material according to claim 2, characterized in that: The mass fraction of polyvinyl alcohol in the polyvinyl alcohol solution in step 1 is 5.0-10.0 wt %.

6. The method for preparing a zirconia framework reinforced polytetrafluoroethylene bionic composite material according to claim 2, characterized in that: The mass fraction of sodium polyacrylate in the sodium polyacrylate solution in step 1 is 40.0-50.0 wt %.

7. The method for preparing a zirconium oxide framework reinforced polytetrafluoroethylene bionic composite material according to claim 2, characterized in that: The heating rate and cooling rate during the sintering process in step 2 are both 5-10° C. / min.

8. The method for preparing a zirconia framework reinforced polytetrafluoroethylene bionic composite material according to claim 2, characterized in that: The heating rate during the sintering process in step 3 is 5-10°C / min.

9. The method for preparing a zirconia framework reinforced polytetrafluoroethylene bionic composite material according to claim 2, characterized in that: The mass fraction of the polytetrafluoroethylene dispersion in step 3 is 40.0-60.0 wt %, and the particle size of the polytetrafluoroethylene particles contained therein is 0.2-0.3 μm.

Citation Information

Patent Citations

  • Polytetrafluoroethylene (PTFE) composite material and preparation method thereof

    CN101613511A

  • Polytetrafluoroethylene composite friction material and preparation method thereof

    CN102942757A